2022
DOI: 10.1159/000526441
|View full text |Cite
|
Sign up to set email alerts
|

From Antiquity to Modern Times: A History of Diabetes Mellitus and Its Treatments

Abstract: The past 200 years have brought an understanding of diabetes and its pathogenesis, as well as the development of treatments that could not have been predicted when the disorder was first clinically described 2000 years ago. Beginning in the late 19th century, the initial descriptions of the microscopic anatomy of the pancreatic islets by Langerhans led to recognition of pancreatic endocrine function. Many investigators attempted to isolate the hypoglycemic factor produced by the pancreas, but Banting, Best, Ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 159 publications
(169 reference statements)
0
2
0
Order By: Relevance
“…Nevertheless, pharmacological treatment should always be combined with lifestyle modifications. It should be noted that dual/ combination therapies either oral or injectable are largely superior to monotherapy (29). Studies conducted by (30,31) have shown an association of physical activity and exercise training with adequate long-term blood glucose control, particularly with decreased levels of glycosylated hemoglobin (HbA1C) and increased insulin sensitivity in patients with T1DM.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, pharmacological treatment should always be combined with lifestyle modifications. It should be noted that dual/ combination therapies either oral or injectable are largely superior to monotherapy (29). Studies conducted by (30,31) have shown an association of physical activity and exercise training with adequate long-term blood glucose control, particularly with decreased levels of glycosylated hemoglobin (HbA1C) and increased insulin sensitivity in patients with T1DM.…”
Section: Discussionmentioning
confidence: 99%
“…In this model, they surgically removed the pancreas (pancreatectomy) from dogs, which led to the development of hyperglycemia and diabetes. This model provided crucial evidence to support the central role of the pancreas in the pathogenesis of diabetes, highlighting the significance of pancreatic dysfunction in T1DM [7]. Particularly, the utilization of this animal model has greatly contributed to significant advancements in comprehending the structure and function of the pancreas, with a particular emphasis on the discovery and molecular mechanisms of insulin [8].…”
Section: Brief History Of Animal Models Of T1dmmentioning
confidence: 94%
“…A adição do termo "mellitus" significa a presença de glicose na urina. Atualmente, o Diabetes Mellitus é amplamente reconhecido como um distúrbio metabólico multifacetado, influenciado por uma combinação de fatores genéticos, ambientais e comportamentais (March, 2022).…”
Section: Diabetes Mellitusunclassified